2022
DOI: 10.3389/fendo.2022.1041718
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the trajectory from intrauterine growth restriction to future obesity

Abstract: During the last decades several lines of evidence reported the association of an adverse intrauterine environment, leading to intrauterine restriction, with future disease, such as obesity and metabolic syndrome, both leading to increased cardiovascular and cancer risk. The underlying explanation for this association has firstly been expressed by the Barker’s hypothesis, the “thrifty phenotype hypothesis”. According to this hypothesis, a fetus facing an adverse intrauterine environment adapts to this environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 173 publications
1
10
0
Order By: Relevance
“…Of those with debt, 58.6% reported more than $200 000 in outstanding student loans. 2 In addition, the majority (78.3%) of respondents felt that their debt would remain a burden after completion of residency, and 66.2% felt it would influence their future job choice, including seeking higher starting salaries and future jobs in less desired locations. This no doubt further contributes to burnout, as surgeons may end up feeling trapped into working longer hours to pay off debt and, because of housing expenses, may choose a job location that favors cost savings over being able to live near a support system of family and friends.We thank the authors for continuing this important discussion.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Of those with debt, 58.6% reported more than $200 000 in outstanding student loans. 2 In addition, the majority (78.3%) of respondents felt that their debt would remain a burden after completion of residency, and 66.2% felt it would influence their future job choice, including seeking higher starting salaries and future jobs in less desired locations. This no doubt further contributes to burnout, as surgeons may end up feeling trapped into working longer hours to pay off debt and, because of housing expenses, may choose a job location that favors cost savings over being able to live near a support system of family and friends.We thank the authors for continuing this important discussion.…”
supporting
confidence: 91%
“…Indeed, we have highlighted a decrease in the rate of macrosomia after MBS; however, we have also reported an increase in the rate of neonates who are small for gestational age. Numerous studies have shown that being small for gestational age is a risk factor for obesity …”
mentioning
confidence: 99%
“…The blood concentrations of anti-VEGF can be detected for up to 2 months (64)(65)(66). Anti-VEGF acts by the destruction of astrocytes leading to reduced brain volume from animal studies (14). A previous review had found significantly lower cognitive scores in infants treated with anti-VEGF (67).…”
Section: Discussionmentioning
confidence: 99%
“…There are also scanty data on some correlation between ROP and behavioural problems, such as autism spectrum disorders (ASD) in extreme preterm infants attributed to poor brain growth (12,13). The pathological process involved in ROP and abnormal neurodevelopmental outcomes share a common pathway (14). It could thus be plausible that ROP could be an independent biomarker for adverse neurodevelopmental outcomes (6).…”
Section: Introductionmentioning
confidence: 99%
“…Of those with debt, 58.6% reported more than $200 000 in outstanding student loans. 2 In addition, the majority (78.3%) of respondents felt that their debt would remain a burden after completion of residency, and 66.2% felt it would influence their future job choice, including seeking higher starting salaries and future jobs in less desired locations. This no doubt further contributes to burnout, as surgeons may end up feeling trapped into working longer hours to pay off debt and, because of housing expenses, may choose a job location that favors cost savings over being able to live near a support system of family and friends.…”
mentioning
confidence: 99%